Repeated daily exposure to 2 ppm nitrogen dioxide upregulates the expression of IL-5, IL-10, IL-13, and ICAM-1 in the bronchial epithelium of healthy human airways. Issue 11 (22nd October 2003) - Pathmanathan, S; Krishna, M T; Blomberg, A; Helleday, R; Kelly, F J; Sandström, T; Holgate, S T; Wilson, S J; Frew, A J
Abstract : Background: Repeated daily exposure of healthy human subjects to NO2 induces an acute airway inflammatory response characterised by neutrophil influx in the bronchial mucosa Aims: To assess the expression of NF-κB, cytokines, and ICAM-1 in the bronchial epithelium. Methods: Twelve healthy, young non-smoking volunteers were exposed to 2 ppm of NO2 /filtered air (four hours/day) for four successive days on separate occasions. Fibreoptic bronchoscopy was performed one hour after air and final NO2 exposures. Bronchial biopsy specimens were immunostained for NF-κB, TNF-α, eotaxin, Gro-α, GM-CSF, IL-5, -6, -8, -10, -13, and ICAM-1 and their expression was quantified using computerised image analysis. Results: Expression of IL-5, IL-10, IL-13, and ICAM-1 increased following NO2 exposure. Conclusion: Upregulation of the Th2 cytokines suggests that repeated exposure to NO2 has the potential to exert a "pro-allergic" effect on the bronchial epithelium. Upregulation of ICAM-1 highlights an underlying mechanism for leucocyte influx, and could also explain the predisposition to respiratory tract viral infections following NO2 exposure since ICAM-1 is a major receptor for rhino and respiratory syncytial viruses.